State of polar climate in 2023 - Ming-Hu Ding; Xin Wang; Lin-Gen Bian; Zhi-Na Jiang; Xiang Lin; Zhi-Feng Qu; Jie Su; Sai Wang; Ting Wei; Xiao-Chun Zhai; Dong-Qi Zhang; Lei Zhang; et al. (Advances in Climate Change Research)
The year 2023 has become the warmest year on global record. As the Antarctic and Arctic are sensitive regions to global warming, the climate changes in 2023 in these regions have attracted widespread attention. In this study, using observations, reanalysis and remote sensing data, we reported detailed polar climate changes in 2023, including warming, sea ice, atmospheric composition and extreme events. Antarctic exhibited large east‒west regional differences and the coexistence of extreme warm and cold events. In Coats Land, Queen Maud Land and the Antarctic Peninsula, three and seven stations recorded the second and third highest autumn air temperatures in history, respectively. The Amundsen–Scott station experienced extreme warming event in July, with the temperature increasing by 40 °C in one day. Abnormal cooling was evident in the Ross Sea and neighboring regions which were predominantly winter (June–August) cold anomalies, with Marylin Station reaching the lowest winter temperature in history. The Arctic experienced the warmest summer after 1979, with an overall distribution of ‘warm land‒cold sea’ on annual average. Compared with the 1991–2020 average, the annual air temperature anomalies reached more than 2 °C in northern Canada and the Barents Sea–Kara Sea coast. Abnormal high summer temperature caused most severe wildfires in Canada on record and second largest daily cumulative melt area over the Greenland ice Sheet daily post-1979. Polar sea ice continued to decrease rapidly, with minimum sea ice extent in Antarctic and Arctic ranking the first and sixth lowest post-1979. For melt season, Arctic Ocean sea ice began to melt later in 2023 than the 2011–2023 average, and freeze onset was delayed due to high temperatures in summer and autumn. Additionally, the status of polar atmospheric greenhouse gases remains bleak, and major greenhouse gas concentrations continue to increase. The Antarctic ozone hole in 2023 formed approximately 10 d earlier and lasted longer than the 1979–2023 average, with a maximum daily area of 2.6 × 107 km2 on 21 September. This summary of polar climate changes in 2023 will help people better understand global climate change and draw attention to polar regions.